On an integral transform - D. Naylor (International Journal of Mathematics and Mathematical Sciences)
This paper establishes properties of a convolution type integral transform whose kernel is a Macdonald type Bessel function of zero order. An inversion formula is developed and the transform is applied to obtain the solution of some related integral equations.